Towards energy leapfrogging in sub-Saharan Africa : exploring strategic investment as a way to increase access to finance among mini-grid energy service companies - Troost, Andre Pieter (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPhil)--Stellenbosch University, 2018.